Using Passive Samplers to Track per and Polyfluoroalkyl Substances (PFAS) Emissions From the Paper Industry: Laboratory Calibration and Field Verification - Hale, Sarah E.; Canivet, Baptiste; Rundberget, Thomas; Langberg, Håkon A.; Allan, Ian J. (Frontiers in Environmental Science, 2021)
Per and polyfluoroalkyl substances (PFAS) are becoming more stringently regulated and as such, a more diverse suite of environmental monitoring methods is needed. In this work a polar organic chemical integrative sampler (POCIS) with a nylon membrane and a combination of Oasis HLB and Fluoroflash® sorbents was calibrated in the laboratory and deployed in the field. A static renewal system was used to determine sampling rates for 12 PFAS which ranged between 0.69 ± 0.27 to 5.68 ± 1.80 L/day. POCIS devices were deployed for 10 days in lake Tyrifjorden, Norway which is known to be contaminated by a closed down paper product manufacturing plant, in order to track the evolution of the PFAS contamination in a river system draining into the lake. This sampling enabled the confirmation of the stretch of river contributing PFAS to lake Tyrifjorden. Freely dissolved concentrations were lowest at the site considered to reflect a diffuse PFAS contamination and highest at the site located downstream of the factory. Perfluorooctanesulfonic acid (PFOS), perfluorohexanoic acid (PFHxA) and perfluorooctane sulfonamidoacetic acid (EtFOSAA) dominated the concentration profile at this site. Emissions of PFAS to lake Tyrifjorden were estimated to be 3.96 g/day for 12 PFAS.